The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1515/cclm.2011.719
|View full text |Cite
|
Sign up to set email alerts
|

External quality assessment of point-of-care International Normalized Ratio (INR) testing in Europe

Abstract: Background: Point-of-care testing (POCT) of prothrombin time, expressed as International Normalized Ratio (INR), is widely used to monitor patients in oral anticoagulation treatment. Guidelines recommend that POCT users should participate in an external quality assessment (EQA) scheme whenever available. The aim of this study was to investigate which European countries provide EQA for POCT INR and to compare how these schemes are organized. Methods: Thirty European countries were invited to participate in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…The Danish quality specification for a method bias of 6% (23 ) was used. The quality specification for a deviating result from method target was set to 15%, which is the most commonly used quality specification for EQA for POC INR in Europe (14 ). One of the likely reasons why this quality specification is wider than the specification for method bias is that it includes random error as well as the systematic error.…”
Section: Combined Assessment Of Poc Inr Methods Bias and Singleparticimentioning
confidence: 99%
See 2 more Smart Citations
“…The Danish quality specification for a method bias of 6% (23 ) was used. The quality specification for a deviating result from method target was set to 15%, which is the most commonly used quality specification for EQA for POC INR in Europe (14 ). One of the likely reasons why this quality specification is wider than the specification for method bias is that it includes random error as well as the systematic error.…”
Section: Combined Assessment Of Poc Inr Methods Bias and Singleparticimentioning
confidence: 99%
“…However, a recent study (14 ) has shown that in most European countries EQA for POC INR testing is not provided, primarily because of the lack of a suitable control material. The study also showed that different types of EQA schemes are provided and all have advantages and limitations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different EQA providers however use a wide range of APS for the same measurand [2][3][4][5]. A survey performed by the European Organisation for External Quality Assurance Providers in Laboratory Medicine (EQALM) in 2014 showed that the criteria used to set the APS also vary widely [6], which is presumably a strong contributor to the variation in APS.…”
mentioning
confidence: 99%
“…1 Patients who have monitored their therapy at home with a point-of-care INR monitor have demonstrated an ability to achieve a high rate of time in a therapeutic range, as documented in clinical trials. 2 Guidelines recommend that POCT users (eg, anticoagulation clinics) should participate in an external quality assessment scheme (EQAS).…”
mentioning
confidence: 99%